Pengaruh Pengendalian Internal, Moralitas Individu, dan Personal Culture Terhadap Kecurangan Akuntansi Pada LPD Se-Kecamatan Abiansemal Kabupaten Badung - Ni Made Fitri Adrian; Sang Ayu Putu Arie Indraswarawati; Ni Wayan Yuniasih (UNHI Press, 2025)
The rapid progress that occurs in accounting science and technology in accounting systems has a very influential impact on various things in the world of economics and business, One of these is the thing called financial scam. There needs to be a lot of internal control to stop theft. The study's goal is to find out how personal culture, values, and internal control are linked to fraud in accounts at LPDs in the Abiansemal Badung District. The Chairman, Treasurer, and Accounting comprised the population of all employees who worked at the LPD in the Abiansemal District, and they were the 104 respondents used in this study. The sampling process was conducted using a practice known as purposeful sampling. Findings from the study showed that internal control, personal morals, and personal culture all had a negative and significant effect on LPD accounting fraud in the Abiansemal Badung District.